Waste reduction guideline for production line using boolean algebra - Mohamad Sazuan, Sarifudin (2022)
Production line in automotive manufacturing industries involves a lot of processes and this can produce a lot of wastes. The accumulated waste from the production line can give an effect on the entire production process. Value Stream Mapping (VSM) can be used to trace wastes from production processes. However, previous studies only focused on eliminating the wastes and did not provide a guideline that can be used by the manufacturer to determine the amount of wastes that should be eliminated from the production line. Therefore, manufacturer needs a guideline in eliminating amount of wastes from production line. The guideline can be used to determine the wastes that need to be eliminated, and only unavoidable or “good” wastes should be retained. The objectives of this research are to develop a model that can produce the elimination of wastes for production line based on Boolean algebra from VSM and to create a guideline in determining the amount of wastes that should be reduced from production line and to validate the model with the company in automotive industry. This research starts with observation and data collection in automotive company. The data are used to draw the Current State Map. The wastes were identified by using Current State Map and were reduced with the Boolean Logic concept. The truth table was constructed based on Logic gates and indicated the combination that can be determined by choosing the minimum activities. Future State Map was developed based on the combination that had obtained from the previous phase. The time normalization had been derived to obtain the most minimum time that needed for benchmark against with others time of different activities. Normalized time was derived which is needed in truth table because this method only allows a single value exists in truth table. The different values of the normalized time need to be reduced to achieve the most minimum requirement of the activities. Meanwhile, the model is able to produce the combinations among the wastes from the Current State Map. The combinations show the total time of the activities that can be considered as the wastes in the production line. The result, Future State Map can be achieved by reducing time consumed of the activities. Consequently, the total time consumed in the Future State Map was reduced and is less than time consumed in Current State Map. As a conclusion, the proposed model can be used by the manufacturer to create the combinations among the wastes to find out the amount of wastes that should be eliminated. The guideline can be used to determine the amount of wastes that should be eliminated in achieving the shortest time of the production line by making continuous reductions on the wastes that exist in production line.